Forming strategic public-private partnerships to establish new health structures for the military health unit located in Melgar, Tolima and Medical Associates SA New Clinic San Sebastian Girardot, Tolima. (2013)
The present test is outlined the degree and the nature of the collaboration between public sector (Military Health FAC) and private sector (Clinic San Sebastian), that affect in the development of the strategies of long term and in the form in which they are implemented across programs and incentives, in a frame of common good. This is what the authors name " alliance public - private road ", fundamental topic developed in the written present.. The selected experiences show that the formulation of agreed by consensus and intelligent strategies, and the institutions public - private road who accompanies her, they have intimate relation with the efficiency of the policies and programs that sustain them.